Misunderstanding the female athlete triad: Refuting the IOC consensus statement on relative energy deficiency in sport (RED-S) - De Souza, M. J.; Williams, N. I.; Nattiv, A.; Joy, E.; Misra, M.; Loucks, A. B.; Matheson, G.; Olmsted, M. P.; Barrack, M.; Mallinson, R. J; Gibbs, J. C.; Goolsby, M.; et al. (British Journal of Sports Medicine, 2014)
An IOC consensus group has recently introduced a new umbrella term, that is, a Relative Energy Deficiency in SportÆ (RED-S) to describe the physiological and pathophysiological effects of energy deficiency in male and female athletes.1 The authors assert that a new terminology is required to more accurately describe the clinical syndrome originally known as the Female Athlete Triad that is a more comprehensive, broader term for the overall syndrome, which includes what has so far been called the Female Athlete Triade. This new terminology (RED-S) is insufficiently supported by scientific research to warrant adoption at this time. The Female Athlete Triad has more than 30 years of published evidence to support its existence in the scientific literature with strong evidence for its clinical sequelae and should remain a focus of scientific inquiry and translation.2û6 Moreover, several major concerns and errors with the IOC consensus statement should give researchers and practitioners great pause before adopting the IOC's new terminology, its theoretical construct and its proposed recommendations for screening and return to play.